No caminho das águas: a trajetória histórica da Vila de Itapemirim e de seu porto (1800-1850) - Machado, Lucas da Silva (2021)
This dissertation aims to study the port of Itapemirim in the first decades of the nineteenth century (1800-1850), addressing social, political and economic issues that surround it. In this sense, using maps and records of parish priests and travelers who traveled through the locality, we seek to analyze the Itapemirim river, from its bar to its sources, traversing the entire historical context, which began in the 16th century, with Portuguese colonization, until the 19th century, providing for the formation of the village of Itapemirim. Thus, I will use the concept of historical time developed by Fernand Braudel, marked by the dialectic of durations, pointing out the dynamics of change and permanence existing in his works, in addition to concepts that address the formation of geographic space. Following this line, the present work analyzes the economic relationship that Itapemirim had with other commercial squares, such as Rio de Janeiro and Vitória, which through their port, through coastal shipping, exported and imported products that moved local and domestic commerce and of all the Espírito Santo.